Unlocking efficient RhB degradation by silver nanowires and porous graphene doped MoTe2: Combined experimental and DFT insights - Afsah Mobeen Haider; Muhammad Ikram; Anwar Ul-Hameed; Ghafar Ali; Souraya Goumri-Said; Mohammed Benali Kanoun (Applied Surface Science Advances)
A novel ternary nanocatalyst (NC) comprising silver nanowires (Ag NWs) and porous graphene (PG) assisted MoTe2 was synthesized via a controlled co-precipitation method for the primary objective of disinfecting contaminated water. A constant 3 % PG improved charge transport, meanwhile (2 and 4 wt. %) Ag NWs effectively regulated MoTe2 growth and recombination dynamics. XRD confirmed the coexistence of monoclinic and rhombohedral phases of MoTe2. Electronic spectroscopy indicated a characteristic absorption in the 400–800 nm range and bandgap energy (Eg) increased from 1.92 to 2.17 eV with the insertion of dopants. FTIR spectra validated the presence of Mo-Te bonding and TEM images illustrated the formation of MoTe2 nanosheets with emergence of porous sheets and Ag NWs with addition of PG and Ag NWs. Notably, 4 wt. % Ag NWs/PG-MoTe2 achieved remarkable 97.28 % rhodamine B (RhB) degradation under acidic conditions attributed to improved charge separation. Density Functional Theory (DFT) calculations used to model and compute the interaction mechanism among RhB and Ag NWs/PG-MoTe2 during adsorption.